Medical Recipes in Two Middle English Manuscripts: London, Wellcome Library, MSS 404 and 5262. - Marqués Aguado, Teresa; Esteban-Segura, María Laura (Uniwersytet Jana Długosza w Częstochowie, 2020)
Recipes in Middle English specialised texts have been the focus of study over the past few decades. In the studies conducted, attention is drawn to particular types of recipes (medical, culinary, etc.) or to the type of production and intended audience (remedyboks and learned texts, addressed either to lay or to learned audiences). The present study analyses a sample of common recipes taken from two apparently unrelated manuscripts holding recipe collections (London, Wellcome Library, MSS 404 and 5262) in order to unearth connections between both texts. To account for these similarities, the linguistic features and the recipe elements of the recipes examined are discussed adopting a contrastive perspective.
Keywords: Literatura inglesa - S.XII-XV - Historia y crítica; Libros de cocina; Middle English; Wellcome 404; Wellcome 5262; Remedy book; Medical recipe